Effectiveness of Digital Music Platforms’ Social Media Interaction on Advertising Trust Using Cognitive Aspects - Anantia, Alviana Aslama; Masnita, Yolanda; Kurniawati, Kurniawati (Manajemen dan Bisnis, 2023)
The COVID-19 pandemic-related economic crisis made many firms to switch their advertising strategy to digital media, with social media being one of the most popular choices due to its lower cost. As a business with rapid growth and being the most popular form of entertainment among internet users, digital music platforms is no exception. Regarding the current phenomenon, it is unknown at this time whether social media marketing is one of the numerous crucial variables causing this service's expansion. Therefore, this research seek to reveal the impact of social media interaction towards advertising trust of digital music platform through knowledge and affection as the cognitive aspects used. This research conducted on a quantitative method with data collection using questionnaires (Google Form), collected from 190 respondents in Jabodetabek whose having subscriptions for at least on one of digital music platform available in Indonesia. The data is analyzed using Partial Least Squares (PLS). The result shows that social media interaction has a significant impact towards advertising trust, both directly and indirectly through knowledge and affection. Among variables tested, the perception of affection is the lowest. It is desired that digital music platform services companies will look into this matter more.